Effect of conservation agriculture on soil fungal diversity in rice-wheat-greengram cropping system in eastern Indo-Gangetic plains of South Asia - Kumar, Rakesh; Choudhary, Jaipal Singh; Naik, Sushanta Kumar; Mishra, Janki Sharan; Banra, Sushmita; Poonia, Shish Pal; Mondal, Surajit; Das, Anup; Rao, Karnena Koteswara; Kumar, Virender; Bhatt, Bhagwati Prasad; Chaudhari, Suresh Kumar; et al. (Frontiers Media, 2024)
Introduction: Conservation agriculture (CA) is emerging as an eco-friendly and sustainable approach to food production in South Asia. CA, characterized by reduced tillage, soil surface cover through retaining crop residue or raising cover crops, and crop diversification, enhances crop production and soil fertility. Fungal communities in the soil play a crucial role in nutrient recycling, crop growth, and agro-ecosystem stability, particularly in agricultural crop fields.